Winter diet of the long-eared owl Asio otus in Slovenia - Tome, Davorin (Acrocephalus, 2000)
Winter diet of the Long-eared Owl Asio otus was investigated at 15 localities across Slovenia, belonging to seven geographical regions (Fig. 1). Of 3,712 prey items found in pellets, small mammals represented more than 98%, with voles Arvicollinae being the most important (Tab. 1). The proportions of Common Vole Microtus arvalis were the only with a significant negative correlation with food niche-breadth (Fig.2 ). Common Vole therefore the main prey for the owl. The most important alternate prey species were: Field Vole Microtus agrestis, mice of the genus Apodemus, Common-pine Vole Microtus subterraneus, and Water Vole Arvicola terrestris. Which of them occurred in higher percentages in the diet was dependent on their geographical distribution and ecological requirements. Field Voles, for example, were present with more than 10% of all prey items only at Ljubljansko barje and Ribniško podolje. This was probably due to the high ground-water level and regular floods in these two regions, which gain some ecological advantages to Field Voles against other small mammals. In the areas with high degree of field cover, on the other hand, the community of small mammals is often dominated by mice. In such areas (Bela krajina, Dravsko podolje, Mursko podolje), the most important alternate prey species for the Long-eared Owl wasWood Mouse Apodemus sylvaticus (Fig. 3).
Keywords: bird; Birds; ptice; Animal nutrition; ornitologija; Ecosystem; malauharica; Seasons; prehrana; food; Feeding behavior